Can Guest Worker Schemes Reduce Illegal Migration? - Amin, Mohammad; Mattoo, Aaditya (World Bank, Washington, DC, 2012)
The authors analyze recent efforts at international cooperation to limit illegal migration, particularly through the use of legal migration avenues like guest worker schemes. They show that while guest worker schemes may be desirable as an avenue of international migration, they are an inefficient instrument to induce cooperation on illegal migration. On the one hand, guest worker schemes suffer from a negative selection problem relative to illegal migration, which tends to erode their attractiveness to source countries. On the other hand, guest worker schemes increase total (legal and illegal) migration which make them a costly compensating device for the host country. Moreover, guest worker schemes create additional pressure on host countries to implement tough laws against illegal immigration even when the host finds such laws undesirable. Thus, less favorable treatment of illegal immigrants, as in California Proposition 187, may be an inevitable rather than incidental outcome of reliance on guest worker schemes. In contrast, countries that are willing to use transfers and other forms of economic assistance to induce source countries to cooperate can afford relatively liberal treatment of illegal immigrants.